Identification of Bacteria Bacillus sp. as a Decomposer of Organic Contaminants of Domestic Wastewater in Kodingareng Island, Makassar City - Indriyasari, Eka; Birawida, Agus Bintara; Ibrahim, Erniwati (Environmental and Public Health Maritime Journal, 2025)
BACKGROUND: Water pollution is a condition where waste is dumped carelessly into waters resulting from production activities or human activities. Domestic wastewater is the biggest cause of damage and pollution in coastal areas in Indonesia. AIM: This study aims to identify the presence of Bacillus sp. as a decomposer of organic pollutants in domestic wastewater on Kodingareng Island, Makassar City. METHODS: The type of research used is quantitative observational research with a descriptive approach. The sampling technique uses grab sampling technique. The sample in this study consisted of 6 samples. RESULTS: The research results obtained from the microbiological identification process in domestic wastewater from Kodingareng Island, Makassar City, namely that 5 samples contained Bacillus sp. and 1 sample contained Enterobacter aerogenes. These bacteria are able to decompose organic pollutants and the resulting domestic wastewater pH ranges from 6.0 - 8.2 while the temperature ranges from 26 - 29˚C, where this figure is the optimum pH and temperature range for the growth of Bacillus sp bacteria. CONCLUSION: The pH and temperature values ​​of Bacillus sp. in domestic wastewater on Kodingareng Island, Makassar City, it was obtained that it met the optimum pH and temperature values ​​for the bacteria Bacillus sp. Based on the identification results, it was found that the bacteria Bacillus sp. in domestic wastewater on Kodingareng Island, Makassar City.